Slovak Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper assesses Slovakia's household and private sector indebtedness against macroeconomic fundamentals, identifies key vulnerabilities from rapid household credit growth, assesses policy responses to date, and presents further policy options. Strong private sector credit growth has persisted for over a decade and resulted in household debt that is high relative to peers. Credit is now growing in riskier segments. Housing prices have also started to reflect pressures from strong credit growth. The paper describes assessments of household and private sector debt levels relative to fundamentals. It also describes the policy response to date and assesses its effectiveness. Econometric analysis suggests that household indebtedness is growing at a faster pace than implied by economic fundamentals. The credit cycle seems to have reached its post-crisis high. The credit cyclogram, compiled by the National Bank of Slovakia, is an aggregation of a set of core and supplementary variables evaluated against distributions of their own historical values to disentangle factors cyclical credit growth.